(untitled) (Communications in Mathematical Research, 2024)
In this paper, a new generalized m-CMP inverse is introduced into the Minkowski space, and its related properties are discussed. Secondly, three different expressions of m-CMP inverse are listed, namely Hartwig-Spindelböck decomposition, full-rank decomposition and integral expression. Finally, the application of the inverse m-CMP equation in solving linear equations is given.